A New Learning Model for the Information and Knowledge Society: The Case of the UOC - Sangragrave, Albert (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2002)
When it was created in 1995, the Universitat Oberta de Catalunya (UOC) served only 200 students and offered two degrees. Today, it has expanded its activities to serve over 20,000 students and 16 official degrees. UOC also offers more than 250 continuing education courses for those wishing to pursue learning opportunities outside of UOC’s official degree programs. As an innovative university, UOC offers a new way of experiencing education, one that is capable of providing answers to an emerging global and universal knowledge society.Today’s rapidly changing world requires revised learning models that allow the widest possible access to knowledge throughout life, in a continuous, comfortable, and simple manner, irrespective of the geographical constraints. Capitalising on the intensive use of new information technologies, UOC is proactively breaking the barriers of space and time by offering an educational model of distance education based on the use of the Internet. Students of UOC’s Virtual Campus now have easy access to a useful and dynamic learning experience wherever they may be. More significantly, each student becomes the centre of a completely personalized educational process. All receive guidance from an accredited teaching team and have access to some of the most innovative didactic resources and services currently available.From the start, UOC was designed to be an exemplar of a new generation of distance education providers capable of creating cooperative interaction not only between students and professors, students and learning materials, but also among students themselves. To support this goal, flexibility, co-operation, personalisation and interactivity are the four pillars of practice upon which UOC’s model is founded.Research is also one of the main objectives UOC has achieved in recent years. Through the creation of the IN3, a research Institute focused on analysing the impact of the Internet on society, the institute is home to a virtual Ph.D. programme, and Edu Lab, which is a laboratory of educational innovation that researches the use of e-learning.The UOC is open to the world, having achieved this objective by maintaining contacts with the principal international knowledge networks. As a result, it is anticipated that the UOC will become an important actor in future e-learning initiatives.